2012
DOI: 10.7314/apjcp.2012.13.8.3927
|View full text |Cite
|
Sign up to set email alerts
|

Literacy and Breast Cancer Prevention: a Population-Based Study from Iran

Abstract: Breast cancer is the most common cancer in women worldwide and the leading cause of death from cancer among women. Evidence suggests that early diagnosis and screening interventions might help to improve outcomes. This population-based study was conducted to determine breast cancer awareness and screening behavior among Iranian women and to examine its association with women's literacy. The study was carried out in two provinces, with 1,477,045 population, located in central and eastern part of Iran. Overall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
4
22
0
Order By: Relevance
“…Higher education and literacy has been associated with better knowledge and awareness of breast cancer issues (Somdatta and Baridalyne., 2008;Khokher et al, 2011;Gürdal et al, 2012;Harirchi et al, 2012;Sathian et al, 2014). A significant proportion of the participants in the present study were educated and their knowledge score prior to the activity was better than the score reported from the university students of Al-Mukalla city in Yemen.…”
Section: Discussionmentioning
confidence: 48%
“…Higher education and literacy has been associated with better knowledge and awareness of breast cancer issues (Somdatta and Baridalyne., 2008;Khokher et al, 2011;Gürdal et al, 2012;Harirchi et al, 2012;Sathian et al, 2014). A significant proportion of the participants in the present study were educated and their knowledge score prior to the activity was better than the score reported from the university students of Al-Mukalla city in Yemen.…”
Section: Discussionmentioning
confidence: 48%
“…In countries with high rate of illiteracy among women, lack of education can influence awareness and also breast cancer screening behavior (Okabio et al, 2006;Altunkan et al, 2008;Harirchi et al, 2012). In the present study, the level of knowledge regarding how to perform a BSE, the age to start doing BSE, the frequency of performing BSE and actually performing BSE increased with increased level of education among women.…”
Section: Discussionmentioning
confidence: 50%
“…Another two studies reported targeting socio-demographic variables were not effective for BSE practice (Parsa et al, 2008;Akhtari-Zavre et al, 2013). In contrast, other studies (Montazeri et al, 2008;Harirchi et al, 2012) reported that literacy was significantly correlated with a greater degree of knowledge about breast cancer, and literate women were significantly more likely to perform breast self examination.…”
Section: Discussionmentioning
confidence: 58%